Competition Law as an Instrument of Protectionist Policy: Comparative Analysis of the EU and the US - Ikejiaku, Brian; Dayao, Cornelia (Utrecht Journal of International and European Law, 2021)
Today, there is a growing fear of resurfacing protectionism, from United States’ trade-war with China, to UK’s Brexit, to the less known trade-restricting measures adopted by countries globally. The General Agreement on Trade & Tariff (GATT), superseded by the World Trade Organisation (WTO) since 1995, rendered the classic forms of protectionism such as tariffs obsolete. However, it did not defeat protectionism; instead, protectionism has evolved through its protean capacity to adapt into new and often undetectable forms, now labelled as ‘murky’ protectionism (e.g. competition law enforcement and the recent bailout packages). It is argued that there are two ways in which States can utilise competition law to impair free-trade and restrict foreign firms’ access to domestic markets: the exemption of certain anticompetitive conduct under national competition law and the strategic application of domestic competition law. This article considers competition law as an instrument of protectionist policy with comparative analysis of the US and the European Union. Using an international political economy (IPE) perspective underpinned by overlapping theories of (legal/political) realism, this article establishes that, while no direct robust empirical evidence of protectionist motivations on competition law enforcement exists, particularly on ‘merger regulation and export cartel exemptions’, the presence of political elements on the decision-making, the wide discretion granted to competition authorities and the ‘sponge’ nature of competition law present an opportunity for the use of competition law for protectionist tendencies.